ANALYSIS OF THE IMPACT OF PALM OIL PLANTATIONS ON THE SOCIAL AND ECONOMIC CONDITIONS OF THE COMMUNITY (CASE STUDY: PT. LANGKAT NUSANTARA KEPONG) - Mastaria Ginting; Clara Veronika Saragi; Widya Elitta Gurusinga; Hafizul Fahmi; Tonggo Joli Rahel Naiborhu; Laura Juita Pinem (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
This study was motivated by the importance of understanding the effects of the palm oil industry on the social and economic conditions of rural communities. The study aims to analyze the influence of social and economic impacts on community perceptions of the presence of PT Langkat Nusantara Kepong in Tanjung Keliling Plantation Village, Langkat Regency. The method used is a descriptive quantitative approach with a case study design and a survey of 100 randomly selected respondents. Interviews, observations, and questionnaires were used to collect data, and multiple linear regression and descriptive statistics were used to analyze it. The results indicate that public perceptions are influenced by both social and economic impacts, but not simultaneously. This research model cannot explain all public perceptions, indicating the presence of other factors beyond the variables studied. It is concluded that economic benefits alone are insufficient to foster positive public perceptions without adequate social support. Implications suggest that companies need to optimize their social role alongside economic activities, while further research is recommended to examine additional variables to achieve a more comprehensive understanding.